GENERAL CHARACTERISTICS OF YEASTS ISOLATED FROM THE MCMURDO DRY VALLEYS REGION, ANTARCTICA (ABSTRACT) (14th Symposium on Polar Biology) - ニシカワ, ジロウ; マツモト, ゲンキ; ナガシマ, ヒデユキ; イイズカ, ヒロシ; NISHIKAWA, Jiro; MATSUMOTO, Genki I.; NAGASHIMA, Hideyuki; IIZUKA, Hiroshi (National Institute of Polar Research, 1993)
P(論文) departmental bulletin paper